2020
DOI: 10.1109/tnsre.2020.3028966
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Rhythmic Cortical Activity Elicited by Whole-Body Balance Perturbations Suggests the Cortical Representation of Direction-Specific Changes in Postural Stability

Abstract: Postural responses that effectively recover balance following unexpected postural changes need to be tailored to the characteristics of the postural change. We hypothesized that cortical dynamics involved in top-down regulation of postural responses carry information about directional postural changes (i.e., sway) imposed by sudden perturbations to standing balance (i.e., support surface translations). To test our hypothesis, we evaluated the single-trial classification of perturbation-induced directional chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
(91 reference statements)
2
10
0
4
Order By: Relevance
“…This section included 8 studies that assessed changes in low-to-high frequency bands in response to unpredicted perturbations in stance ( n = 5) [ 49 , 77 , 79 , 81 , 82 , 83 , 85 ], walking ( n = 2) [ 86 , 88 ] and multiple tasks ( n = 1) [ 48 ] (stance and walking) ( Table 3 ). While a majority of these studies included young adults ( n = 5), one study examined cortical activations in healthy older adults [ 85 ] and two studies compared cortical activations in people with chronic cortical stroke [ 49 ] and chronic traumatic brain injury [ 83 ] with healthy counterparts. Studies analyzed changes in cortical frequencies including alpha (7.5–12.5 Hz), beta (13–30 Hz), gamma (40–100 Hz) and theta (4–8 Hz).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This section included 8 studies that assessed changes in low-to-high frequency bands in response to unpredicted perturbations in stance ( n = 5) [ 49 , 77 , 79 , 81 , 82 , 83 , 85 ], walking ( n = 2) [ 86 , 88 ] and multiple tasks ( n = 1) [ 48 ] (stance and walking) ( Table 3 ). While a majority of these studies included young adults ( n = 5), one study examined cortical activations in healthy older adults [ 85 ] and two studies compared cortical activations in people with chronic cortical stroke [ 49 ] and chronic traumatic brain injury [ 83 ] with healthy counterparts. Studies analyzed changes in cortical frequencies including alpha (7.5–12.5 Hz), beta (13–30 Hz), gamma (40–100 Hz) and theta (4–8 Hz).…”
Section: Resultsmentioning
confidence: 99%
“…Pathological populations: Unpredicted perturbations only: Solis-Escalante et al [ 49 ] exposed people with chronic stroke and young adults to unpredicted stance perturbations via movable platform. This study reported perturbation direction-specific pictographic presentations of theta band activation patterns similar in both groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results proved that the P2 component was laterized in the right hemisphere for right perturbations and vice versa, which is in conflict with previous studies and could be described by different EEG setups and analyzing procedures. Additionally, it was shown that the forward and backward perturbations can be decoded by using the spectral information (3–10 Hz) of brain signals in the frontocentral areas 58 . Our findings provide evidence that direction-specific instability was encoded across the fronto-centro-parietal region, which is in accordance with the reported study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [11,13,32] have attempted to identify an early cortical sign of postural instability. A negative potential (N1) generated over the fronto-central region, around 100-200 ms following naturally occurring instability while standing still [14] or following external perturbation of the support surface [6,7,9,10,17,19,21,22] has been suggested to indicate the involvement of higher-order processing in the form of detecting an error due to the difference between anticipated and actual postural states and signaling functional postural responses, if necessary [9,10,13,27,32]. These findings suggest that the occurrence of N1 would always indicate a presence of postural instability, regardless of its cause.…”
Section: Introductionmentioning
confidence: 99%